Nigakinone alleviates DSS‐induced experimental colitis via regulating bile acid profile and FXR/NLRP3 signaling pathways. (23rd August 2022) - Liu, Fangle; Yao, Yufeng; Wang, Qian; Zhang, Fengxue; Wang, Meiqi; Zhu, Chenchen; Lin, Chaozhan
Abstract: The correlation of bile acid (BA) metabolism disorder with the pathogenesis of ulcerative colitis (UC) is realized nowadays. Farnesoid X receptor (FXR), a controller for BA homeostasis and inflammation, is a promising target for UC therapy. Nigakinone has potential therapeutic effects on colitis. Herein, we investigated the anti‐UC effects and mechanism of nigakinone in colitic animals induced by dextran sulfate sodium (DSS). The related targets involved in the nucleotide‐binding oligomerization domain, leucine‐rich repeat, and pyrin domain‐containing 3 (NLRP3) signaling pathway were measured. BA‐targeted metabolomics was employed to reveal the regulatory effects of nigakinone on BA profile in colitis, while expressions of FXR and its mediated targets referring to BA enterohepatic circulation were determined. The critical role of FXR in the treatment of nigakinone for colitis was studied via molecule‐docking, dual‐luciferase reporter® (DLR™) assays, FXR silencing cells, and FXR knockout mice. Results showed nigakinone attenuated DSS‐induced colitis symptoms, including excessive inflammatory response by NLRP3 activation, and injury of the intestinal mucosal barrier. Nigakinone regulated BA disorders by controlling cholesterol hydroxylase and transporters mediated by FXR, then decreased BA accumulation in colon. Molecular‐docking and DLR™ assays indicated FXR might be a target of nigakinone. In vitro, nigakinone restrained BA‐induced inflammation and cell damage via FXR activation and inhibition of inflammatory cytokines. However, ameliorating effects of nigakinone on colitis were suppressed by FXR knockout or silencing in vivo or in vitro. Taken together, nigakinone ameliorated experimental colitis via regulating BA profile and FXR/NLRP3 signaling pathway.